r-mode seen in a frame rotating with the star - (:unkn) unknown (My University, 2005)
The figure on the right shows the same oscillating star, now as seen by an observer rotating with the star. The red dots now do not rotate, and the the black lines show the pattern of the mode rotating backwards -- in a direction opposite to the star's rotation.